Dampak Penggunaan Instagram Terhadap Bisnis dan Sebaran Informasi - Irsandi, M Ficky; Sulthon, Muhammad Zahran (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to analyze the impact of Instagram usage on business and information dissemination. Using a qualitative approach through a case study method, this study involved semi-structured interviews with 40 participants consisting of active Instagram users, business actors. The results of the study indicate that Instagram acts as an effective marketing tool, allowing businesses to increase brand visibility and reach a wider audience. Features such as Instagram Stories, IGTV, and Instagram Shopping have proven to be useful in attracting customer attention and facilitating transactions. In the context of information dissemination, Instagram allows for the rapid and wide distribution of news and educational content. User experiences vary, including social and creative benefits, but also raise concerns about potential addiction and privacy issues. This study provides valuable insights into the role of Instagram in business and information dissemination, and highlights the importance of wise use to maximize benefits and minimize risks.